2020
DOI: 10.1103/physrevb.101.205412
|View full text |Cite
|
Sign up to set email alerts
|

Low-loss two-dimensional plasmon modes in antimonene

Abstract: The effects of spin-orbit (SOC) and electron-phonon coupling on the collective excitation of doped monolayer Sb2 are investigated using density functional and many-body perturbation theories. The spin-orbit coupling is exclusively important for the monolayer Sb2 and it leads to the reconstruction of the electronic band structure. In particular, plasmon modes of monolayer Sb2 are quite sensitive to the SOC and are characterized by very low damping rates owing to small electron-phonon scatterings. Our results sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…Optical absorption, phonon-induced damping, and electron excitation spectrum.-In this section, we present a short theoretical description of optical absorption quantities in the long-wavelength limit (q ≈ 0) by making use of the current-current response tensor Π µ (q, ω) calculated within DFT, where the electromagnetic interaction is mediated by the free-photon propagator. The thorough description of the method can be found in our previous works [42,55,56].…”
Section: Methodsmentioning
confidence: 99%
“…Optical absorption, phonon-induced damping, and electron excitation spectrum.-In this section, we present a short theoretical description of optical absorption quantities in the long-wavelength limit (q ≈ 0) by making use of the current-current response tensor Π µ (q, ω) calculated within DFT, where the electromagnetic interaction is mediated by the free-photon propagator. The thorough description of the method can be found in our previous works [42,55,56].…”
Section: Methodsmentioning
confidence: 99%
“…Monolayer WTe2 is a quantum spin-Hall insulator [247] and possesses gate induced superconductivity [248] , while bilayer WTe2 is ferroelectric [249] . Torbatian et al predicted WTe2 single-layer hosts hyperbolic plasmons according to density-functional and many-body perturbation theories [250] . The hyperbolic behavior could be tuned from the FIR to NIR region by chemical doping or strain.…”
Section: Polaritons Of Anisotropic 2d Materialsmentioning
confidence: 99%
“…It means that in one direction they behave like as a dielectric with a positive permittivity, while in the other direction they reveal metallic feature with negative permittivity. These materials become more noteworthy by considering their tunability via chemical doping, gating and strain [12] or temperature [13]. Some anisotropic 2D materials were predicted to show a hyperbolic surface plasmon polariton, but has not confirmed experimentally yet [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, modulation of the hyperbolicity can be affected by the temperature [15]. It has been shown that as temperature increases the in-plane anisotropy of the optical response of T d − W T e 2 and its hyperbolic regime is changed [12]. This suggests T d − W T e 2 is a perfect and promising hyperbolic material for planar optoelectronics and nanophotonics applications.…”
Section: Introductionmentioning
confidence: 99%